Fitting Dynamic Models to Animal Movement Data: The Importance of Probes for Model Selection, a Reply to Franz and Caillaud - Dalziel, Benjamin D. (2010)
Analyzing animal movement can provide a useful perspective on the interface between landscape patterns and individual behavior (Patterson et al. 2008; Schick et al. 2008). In Dalziel et al. (2008) we proposed a method of fitting dynamic movement models to trajectory and landscape data. The goal was to explore how disparate landscape-behavior processes combine to generate animal movement patterns. As an example of the approach, we used a genetic algorithm (GA) to fit artificial neural network (ANN) models to observations of elk (Cervus canadensis) movement.